(untitled) (Damascus University Journal of agriculture sciences, 2022)
The experiment was carried out in the Rabbit House at the Faculty of Agriculture- Damascus University on 20 local female rabbits (one year old and weighing about 3.6kg) The experiment aimed to determine the effect of adding Xylanase Enzyme to diets on some reproductive and production indicators of local female rabbits. Rabbits were distributed into 4 groups (5 rabbits/group) according to the percentage of the enzymatic additive added, Group1 (control) without enzymatic additive, whereas 0.2, 0.4 and 0.8 g of enzymatic additive was added to 1 kg of the diet in Groups 2,3 and 4, respectively. Rabbits were fed on 4 diets of which materials were identical in their proportions but different in the amount of the enzymatic addition. Results showed positive improvement in the experimental groups for the reproductive and productive indicators studied (fertilization ratio, litter size, live weight of births, mortality rate during lactation, amount of feed consumed during pregnancy and lactation), but this improvement was not significant, compared with the control group.